Polka dot cementless talar component in enhancing total ankle replacement fixation: A parametric study using the finite element analysis approach. (February 2022) - Mohd Moideen, Irwan Shah; Lim, Chin Tat; Yeow, Raye C.H.; Chong, Desmond Y.R.
Abstract: The primary stability of a total ankle replacement (TAR) is essential in preventing long-term aseptic loosening failure and could be quantified based on micromotion at the bone-prosthesis interface subjected to physiological loading during the normal walking. A 3D finite element analysis was conducted to investigate the current commercial STAR™ Ankle TAR bone-prosthesis interface relative micromotion (BPIRM) with addition of the talus bone minimum principal bone stresses (MPBS). Comparison was made to the proposed polka dot designs with the hemispheric feature that was demonstrated to enhance BPIRM. Parametric studies were conducted on the hemispheric features with changes in its diameter, length and shape. The FE results indicated high BPIRM at the talar component was primarily contributed by de-bonding (in the normal direction) between the talus bone and talar component. The MPBS were found to be most significant in the superior anterior and superior medial regions of the talus bone. When the pin length was increased from 1.5 to 3 mm, the BPIRM was predicted to fall below 50 μm in favour of bone in-growth. Based on the practicality of the prosthesis implantation during the surgical procedure, the final design that incorporated both the initial polka dot and 3 mm pin length in a crisscross manner was deemed to be a favorable design with reduced BPIRM and MPBS hence lowering the risk of long-term aseptic loosening. Highlights: Validated FEA model showed high bone-prosthesis interface micromotion was concentrated at posterior of the talar component. Polka dot design was found to improve bone-prosthesis interface micromotion and parametric design features were introduced. High interface micromotion at talar component was primarily contributed by de-bonding between the bone and component. Polka dot with 3 mm pin length in crisscross manner was deemed favorable in lowering risk of long-term aseptic loosening.